Investigating the Impact of Supply Chain Dynamics on Financial Performance with Supply Chain Disruption Structure Approach - Ebrahim Farbod; Alireza Hamidieh; Hootan Amininia (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: This research aims to investigate the effect of supply chain dynamics and flexibility in the face of disruptions on financial performance with the mediating role of supply chain resilience.Methodology: The present study is descriptive-correlational regarding purpose and data collection. The statistical sample of the present study is 217 business managers of pharmaceutical companies according to the formula for determining the sample size of Cochran, observing the success ratio in this research and considering the error coefficient of 0.05. All extracted data are analyzed using SPSS23 and SmartPls statistical software in the inferential statistics section. Analysis of variance-based structural equations has been used to analyze the data.Findings: The study results show that the dynamics and flexibility of the supply chain in the face of disruptions affect financial performance with the mediating role of supply chain resilience. Supply chain flexibility is also affected by the direction of supply chain disruption. However, the financial performance effects on supply chain disruption orientation can be controlled through supply chain flexibility.Originality/Value: The study results can help design a strategic resilience plan for pharmaceutical companies. Accordingly, it proposes to supply chain managers that when faced with disruptions, the dynamics and flexibility of the supply chain should be increased to improve network resilience.